2021
DOI: 10.15446/ing.investig.v41n2.84539
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dynamic and Fuzzy Value Stream Mapping (DFVSM): System Dynamics and Fuzzy Logic Integration

Abstract: Value stream mapping (VSM) is a method to identify waste and activities that do not add value. One of its main disadvantages is that the parameters used in the process and material flows are deterministic. The motivation of this research is to improve the reliability of the estimation of the lead time in VSM, transitioning from a static model to a dynamic model that incorporates uncertainty and imprecision in the data, as well as to develop a novel dynamic and fuzzy value stream mapping (DFVSM) based on integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Huang et al (2019) suggested a multi-layer DVSM that combines conventional VSM with a multi-agent system built on CPS technology, automatically gathers data close to the workstation through an agent and displays many parts in the manufacturing process and materials in real-time or almost real-time. To increase the dependability of scheduled delivery timeframes, Serrato (2021) created a dynamic and fuzzy VSM based on integrated SD and fuzzy logic that includes uncertainty and ambiguity into the percentage of efficiency and overall equipment effectiveness (OEE). The researchers are merging VSM and the Industrial IoT (IIoT) in addition to radio frequency identification (RFID) and cyber physical system (CPS) technologies.…”
Section: Literature Researchmentioning
confidence: 99%
“…Huang et al (2019) suggested a multi-layer DVSM that combines conventional VSM with a multi-agent system built on CPS technology, automatically gathers data close to the workstation through an agent and displays many parts in the manufacturing process and materials in real-time or almost real-time. To increase the dependability of scheduled delivery timeframes, Serrato (2021) created a dynamic and fuzzy VSM based on integrated SD and fuzzy logic that includes uncertainty and ambiguity into the percentage of efficiency and overall equipment effectiveness (OEE). The researchers are merging VSM and the Industrial IoT (IIoT) in addition to radio frequency identification (RFID) and cyber physical system (CPS) technologies.…”
Section: Literature Researchmentioning
confidence: 99%